2016
DOI: 10.1177/1474704916651270
|View full text |Cite
|
Sign up to set email alerts
|

Online Female Escort Advertisements

Abstract: Female escorts represent an occupational group that charges a fee for sex, which can be regarded as an extreme form of shortterm mating. The present study examined if the fees charged by escorts are related to traits typically associated with female shortterm mate value. A total of 2,925 advertisements for female escorts offering sexual services in the United States were examined, as a customized software program was used to download all the advertisements from an online escort directory. The advertisement con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 53 publications
2
23
0
1
Order By: Relevance
“…However, out-calls are consistently more expensive than in-calls, with the median out-call 1.26 times larger than the in-call on average. The finding that out-calls are consistently more expensive than in-calls is corroborated by past research conducted on the advertisements of US sex workers (Griffith et al, 2016).…”
Section: Views Rates Ratings and Time Active On Platformsupporting
confidence: 56%
“…However, out-calls are consistently more expensive than in-calls, with the median out-call 1.26 times larger than the in-call on average. The finding that out-calls are consistently more expensive than in-calls is corroborated by past research conducted on the advertisements of US sex workers (Griffith et al, 2016).…”
Section: Views Rates Ratings and Time Active On Platformsupporting
confidence: 56%
“…Similar association between age and other cues to female fertility have been found in a study of Polish prostitutes (Prokop et al, 2018): physical signs of fertility in female prostitutes predict the prices of sexual services, and women showing better signs of fertility offer their services at higher prices. A study conducted with American female escorts (a common euphemism for sexual services) found that younger women charged higher fees than their older counterparts (Griffith et al, 2016). The costs of sex are apparently higher for young escorts.…”
Section: Introduction Transactional Sexmentioning
confidence: 99%
“…While some temporal variations do exist (consistent with the fact that the waist-to-hip preference is a near-universal), the general hourglass effect holds across these studies. The commercial premium that men place on the hourglass figure was captured by Griffith et al (2016) in their analysis of online ads of female escorts. Specifically, online female escorts who advertise the hourglass figure charge higher fees.…”
Section: The Hourglass Figure: Socially Constructed Beauty Marker or mentioning
confidence: 99%